Strategi Pemasaran Pendidikan Interaktif di SD IT Al Bukhori School Banyuasin - Iqbal, Muhammad; Annur, Saipul; Kanada, Rabial (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This research aims to analyze the interactive education marketing strategy at Al Bukhori School in Banyuasin, and identify inhibiting and supporting factors for the implementation of this strategy. Conducted at Al Bukhori School, Jl Meritai Raya Perumahan Anggrek Indah Banyuasin, this study employs a qualitative approach with qualitative descriptive methods. Data is acquired through field observations and in-depth analysis to provide insights into the interactive education marketing strategy. The research findings indicate that product, price, promotion, and people are key indicators in the interactive education marketing strategy. This strategy focuses on a positive image through school community relations and appropriate pricing. It is discovered that promotion and people's involvement play a crucial role in the success of marketing educational services. However, the research also identifies inhibiting factors, such as financial constraints and a lack of public awareness about interactive education.